2022
DOI: 10.3389/fphys.2022.916278
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Sarcolemmal Background Ca2+ Entry and Sarcoplasmic Ca2+ Leak Currents on Electrophysiology and Ca2+ Transients in Human Ventricular Cardiomyocytes: A Computational Comparison

Abstract: The intricate regulation of the compartmental Ca2+ concentrations in cardiomyocytes is critical for electrophysiology, excitation-contraction coupling, and other signaling pathways. Research into the complex signaling pathways is motivated by cardiac pathologies including arrhythmia and maladaptive myocyte remodeling, which result from Ca2+ dysregulation. Of interest to this investigation are two types of Ca2+ currents in cardiomyocytes: 1) background Ca2+ entry, i.e., Ca2+ transport across the sarcolemma from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…SR Ca 2+ leak did not significantly affect resting membrane potential and exhibited only a marginal positive correlation with action potential duration. In another in situ study of a human ventricular myocyte, modulating SR Ca 2+ leak had negligible effects on both resting membrane potential and action potential duration at any pacing frequency (Streiff and Sachse, 2022). It seems unlikely that TRPC1 leak has a role in modulating myocyte electrophysiology in physiological conditions.…”
Section: The Debate Of Trpc1 Mechanosensitivitymentioning
confidence: 95%
See 2 more Smart Citations
“…SR Ca 2+ leak did not significantly affect resting membrane potential and exhibited only a marginal positive correlation with action potential duration. In another in situ study of a human ventricular myocyte, modulating SR Ca 2+ leak had negligible effects on both resting membrane potential and action potential duration at any pacing frequency (Streiff and Sachse, 2022). It seems unlikely that TRPC1 leak has a role in modulating myocyte electrophysiology in physiological conditions.…”
Section: The Debate Of Trpc1 Mechanosensitivitymentioning
confidence: 95%
“…Another potential pathologic consequence of chronically increased SR leak through TRPC1 channels is increased susceptibility to arrhythmia. As has been discussed, primarily in the context of RyR leak, chronically increased SR leak makes cardiomyocytes increasingly susceptible to arrhythmias (Hannanta-Anan and Chow, 2016;Siri-Angkul et al, 2021;Streiff and Sachse, 2022). Indeed, recent studies suggested a link between TRPC-mediated currents and arrhythmogenesis (Wen et al, 2018;Siri-Angkul et al, 2021).…”
Section: The Debate Of Trpc1 Mechanosensitivitymentioning
confidence: 99%
See 1 more Smart Citation
“…Decreased calcium influx into cells reduces fibroblast differentiation, collagen release, and reduce TGF-β-induced fibrotic remodeling ( Ramires et al, 1998 ; Teng et al, 2015 ). Intracellular Ca 2+ signals are generated by Ca 2+ entry through Ca 2+ -permeable channels in the plasma membrane and by Ca 2+ release from intracellular Ca 2+ stores ( Feng et al, 2019 ; Maione et al, 2022 ; Streiff and Sachse, 2022 ). Intracellular Ca 2+ level is also precisely controlled by plasma membrane ATPase (PMCAs), Na + /Ca 2+ exchangers (NCX) and sarcoplasmic reticulum Ca 2+ -ATPase (SERCA) ( Kranias and Hajjar, 2012 ; Morotti et al, 2021 ).…”
Section: Effects Of Ion Channels On Fibroblast Differentiation or Myo...mentioning
confidence: 99%